Conference Review: 6th Experimental Archaeology Conference, York 2012 - Ruth Fillery Travis (EXARC Journal, 2012)
Established in 2006 with a workshop at UCL London, the Experimental Archaeology Conference is an annual event aiming to bring together experimental practitioners from Europe and afield. Since 2006 it has been held at a variety of locations in England and Scotland, with twelve to fifteen papers presented each year over two days, in addition to demonstrations and posters.